Right iliac fossa kidney: Differential diagnoses. Issue 3 (5th January 2021) - Doherty, Daniel T.; Wolowczyk, Leszek
Abstract: A right iliac fossa kidney is rarely encountered by the general clinician but multiple diagnoses should be considered. Abstract : A right iliac fossa kidney is rarely encountered by the general clinician but multiple diagnoses should be considered.